MARXIST PERSPECTIVES: ANALYZING THE TRIPARTITE ROLE OF MASSES IN HISTORICAL DEVELOPMENT - Ying, Wang Xiu; Min, Zhang Lei (International Research Journal of Arts and Communication, 2024)
Karl Marx's intellectual journey yielded two momentous discoveries that continue to shape our understanding of socio-economic dynamics and human society. The first is the theory of surplus value, unraveling the mechanisms of capitalist exploitation, while the second is historical materialism, a profound exploration into the enigmatic tapestry of human civilization. At the heart of Marxist historical materialism lies the mass view of history, a pivotal concept that evolved during Marx's formulation of this socio-historical framework. The Marxist perspective on mass history is firmly rooted in the objective and perceptive majority, commonly known as "the masses," and underscores their pivotal role as the driving force behind historical development. Anchored in the inexorable march of societal progress and varying degrees of connection between individuals and history, this viewpoint scientifically posits that the masses are the true agents of change. For the first time, the mass view of history comprehensively and scientifically validates the historical agency of the masses, affirming that social existence shapes social consciousness and confirming the decisive influence wielded by the masses in shaping history and the course of historical evolution. The Marxist mass view of history encompasses three distinct dimensions: the masses as creators of history, the masses as active participants in cognitive endeavors, and the masses as bearers of social value.